Silica Nanoparticles for Biomedical Application: Challenges and Opportunities - Mun, E.A.; Zhaisanbayeva, B.A. (Eurasian Journal of Applied Biotechnology, 2020)
Over the past few decades, nanoparticles have been attracting significant attention of researches in chemical, biomedical, pharmaceutical sciences, due to their unique physicochemical properties. This includes ultra small size, large surface area, good biocompatibility and high reactivity. In particular, nanoparticles are promising for pharmaceutical and biomedical fields, as they can be applied as drug carriers and diagnostic tools. Among nanomaterials for biomedical application, silica nanoparticles exhibit great potential due to their straightforward synthesis and separation, low cost, safety, biocompatibility and possibility to further functionalization. Silica nanoparticles have been attractive for pharmaceutical science due to their unique properties, such as tunable size, high surface area and large pore volume, and potential in biomedical application as drug and gene delivery vectors and bioimaging agents. However, some of their properties remain poorly investigated. This short communication discusses the main routes for synthesis of silica nanoparticles, their properties and opportunities for their application in pharmaceutical and biomedical industries, as well as a few challenges in the development of silica-based systems that need to be overcome.